Pengaruh Pengetahuan Zero Waste Food Terhadap Implementasi dalam Kegiatan Praktik Kuliner Oleh Mahasiswa S1 PKK Tata Boga - Amanda Ramadhani Safitri; Anni Faridah; Kasmita Kasmita; Wiwik Gusnita (SENTRI: Jurnal Riset Ilmiah, 2025)
Food waste remains a critical challenge in achieving sustainable food systems, particularly in vocational culinary education where practical activities frequently generate food residues. Although the concept of zero waste food has been widely promoted, empirical evidence examining how students’ knowledge influences its implementation in higher education culinary practice is still limited, especially within Indonesian vocational teacher education programs. This study aims to analyze the influence of zero waste food knowledge on its implementation in culinary practice activities among undergraduate students of the S1 PKK Tata Boga program at Universitas Negeri Padang. Using a quantitative ex post facto design, the study involved 76 students selected through proportional random sampling. Data were collected using validated questionnaires measuring zero waste food knowledge and implementation, and analyzed using descriptive statistics, assumption tests, and simple linear regression. The results show that both students’ knowledge and implementation of zero waste food are generally at a moderate level. Regression analysis indicates a positive and statistically significant influence of knowledge on implementation (t = 3.383, p = 0.001), with a coefficient of determination of 13.4%. This finding suggests that knowledge contributes meaningfully to sustainable culinary practices, although it is not the sole determinant, as other factors such as attitudes, habits, learning experiences, and institutional support also play a role. The novelty of this study lies in providing empirical evidence on the extent to which zero waste food knowledge is translated into practice within a vocational teacher education context. The findings offer practical implications for curriculum development and learning strategies that integrate sustainability-oriented knowledge with hands-on culinary practice to reduce food waste.